2023
DOI: 10.1021/acs.langmuir.2c03200
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Microstructure, Hybridization, and Internal Stress of Al-Doped Diamond-Like Carbon Coatings: A Molecular Dynamics Simulation

Abstract: This work modified some parameters related to the bond order in REBO-II of the C−C interaction and simulated the ta-C:Al film deposition using the large-scale atomic/molecular massively parallel simulator especially focused on the effect of the Al-doping content on the microstructural and mechanical properties of tetrahedral amorphous carbon films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Guo et al (2017) synthesized Al/Ti-doped DLC coatings using a unique hybrid ion-beam system and observed a minimum σ of 1.28 ± 0.1 GPa and maximum H of 20 GPa. Huang et al (2023a) analyzed the tetrahedral carbon aluminum film using a large-scale atomic parallel simulator and observed that Al plays a significant role in the properties of the developed coating. Wongpanya et al (2022) synthesized a DLC coating with Al and N doping over AISI 4140 steel using the filtered cathodic vacuum-arc technique and observed that the corrosion resistance and adhesion performance of the developed coating significantly enhanced compared to those of DLC coating.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Guo et al (2017) synthesized Al/Ti-doped DLC coatings using a unique hybrid ion-beam system and observed a minimum σ of 1.28 ± 0.1 GPa and maximum H of 20 GPa. Huang et al (2023a) analyzed the tetrahedral carbon aluminum film using a large-scale atomic parallel simulator and observed that Al plays a significant role in the properties of the developed coating. Wongpanya et al (2022) synthesized a DLC coating with Al and N doping over AISI 4140 steel using the filtered cathodic vacuum-arc technique and observed that the corrosion resistance and adhesion performance of the developed coating significantly enhanced compared to those of DLC coating.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-enhanced chemical vapor deposition (PECVD) is a popular CVD technique used for depositing Al-DLC films since it produces high-quality films at relatively low temperatures (Huang et al, 2023b). In PECVD, a gaseous mixture of hydrocarbon and aluminum precursors in a reaction chamber is subjected to electrical discharges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations